The All Eyes on Rafah Hashtag Digital Social Movement on TikTok Platform - Dewi Susantin; Agus Saifuddin (Al-Amru: Jurnal Komunikasi dan Dakwah Islam, 2025)
At the end of May 2024, social media was shocked with the trending topic #AllEyesOnRafah, this was due to the collective efforts of netizens who utilized the power of social media to convey this humanitarian message. With this tragedy, the trending topic #AllEyesOnRafah reached 37 million posts on social media. This hashtag emerged as a form of solidarity and to draw world attention to events in the city of Rafah, especially regarding military attacks and the increasingly deteriorating humanitarian conditions. The reason researchers prefer the TikTok platform as one of the research objects is because this application has a high number of users and daily active users throughout the world, especially among young people. The platform also provides insight into how young people mobilize and participate in social movements. The research method used is descriptive qualitative with a content analysis approach, data collection techniques using documentation methods and data analysis techniques, namely social interaction analysis methods to provide detailed and clear information and descriptions in a systematic and objective manner. After conducting research, it can be concluded that the role of social media in campaigns such as the hashtag All Eyes on Rafah is very significant. This platform is able to connect individuals from various parts of the world, create global solidarity, and facilitate important communication or dialogue. However, to achieve maximum impact, challenges or obstacles such as information management must be managed wisely, this shows the importance of a careful approach in utilizing social media as a tool for social and political change.